Further Evidence That the CFTR Variant c.2620-6T>C Is Benign. (9th January 2017) - Wallerstein, Violet I.; Wallerstein, Robert
Abstract : The c.2620-6T>C variant in the CFTR gene is a rare variant about which little is known. We present an asymptomatic adult who has this variant as well as the well described delta F508 pathogenic variant in transpresentation. This patient provides additional evidence that this is a benign polymorphism.